Pneumonia Vaccines: Indications for Use and Current Safety Data in Pregnancy - Dutra, Karley; Berry, Hayley; Lazenby, Gweneth B. (American Journal of Perinatology, 2025)
Streptococcus pneumoniae is a leading cause of pneumonia, meningitis, and invasive pneumococcal disease among adults in the United States, with higher rates of disease occurring among individuals with chronic medical and immunocompromising conditions. Pregnant individuals, especially those with comorbid conditions, are also at increased risk of infection due to S. pneumoniae due to physiological and immunologic changes in pregnancy. Vaccination against pneumococcus is recommended for adults living with HIV aged 19 to 49, congenital or acquired immunodeficiency, asplenia, chronic renal failure, sickle cell disease, alcohol abuse, cerebrospinal fluid leaks, congestive heart failure and cardiomyopathies, chronic lung disease, chronic liver disease, and diabetes mellitus. During pregnancy, the American College of Obstetricians and Gynecologists (ACOG) recommends vaccination against S. pneumoniae for individuals meeting the criteria for immunization outside of pregnancy. Pneumococcal vaccine uptake has been low. There are no data available for vaccine uptake in pregnancy, but we suspect it is lower than nonpregnant populations. Low uptake of immunization rates in pregnancy is likely multifactorial and includes general vaccine hesitancy among pregnant individuals, cost, access to care, and supply shortages. While data in support of pneumococcal vaccines during pregnancy are limited, sufficient evidence exists to support the safety and efficacy of vaccination in the antepartum period. Pregnancy provides an opportunity to continuously engage individuals in care, allowing obstetricians and gynecologists to establish rapport, work to reduce vaccine hesitancy, and to provide pneumococcal immunization to those who are eligible. Medical indications for pneumococcal vaccination will increasingly apply to pregnant persons as the population acquires comorbidities and there is a need for improved education among obstetricians on the topic of antenatal pneumococcal vaccination.
Keywords: Streptococcus pneumoniae; antenatal vaccination; pneumococcal vaccination; high-risk pregnancy; HIV; vaccine hesitancy